IMPLEMENTASI PEMISAHAN TRAFIK IIX DAN INTERNASIONAL DENGAN OPTIMASI BANDWIDTH - Herman Kuswanto (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
In line with the development of information technology very rapidly, the intensity of use of the internet network through a transmission cable and wireless increased even very dense. As a result, felt all right to slow internet connection due to the limited bandwidth available. To address these problems required an increase in quality of service (quality of services / QoS). One way to improve the quality of service (QoS), Internet usage is by separating the connection based on the goals that will be accessed by the user whether or International IIX connections, while providing bandwidth sharing with different limits according to user needs. To deal with this problem weneed a separate tool or application to connect at the same time melakuakan International IIX and bandwidth allocation more efficient use of bandwidth in order to simplify network managementand Internet in particular is connected to a LAN. Tool or application that can support the function of the separation of traffic and bandwidth sharing is a router, Mikrotik Router Os is one of theoperating systems that provide separation of traffic and bandwidth sharing. On Mikrotik RouterOS will be implemented separation IIX and International traffic with bandwidth sharing, in this study proved to be dealing with the problem by splitting the traffic bandwidth IIX andInternational.